Beyond compliance : the refinery manager's guide to ISO 14001 implementation - Cheremisinoff, Nicholas P. (Gulf Pub., 2006)
This book offers refineries a practical guide for implementing environmental management systems (EMS). The author, who has implemented hundreds of successful EMS programs throughout North America, Europe, Russia and the Middle East, provides a detailed explanation of what an EMS is and how it can benefit refinery operations in complying with environmental laws and improving the overall efficiency of their operations. The author's approach has been internationally recognized as an integrated model that captures improved compliance and financial savings by reducing operating costs through dedicated pollution prevention programs.
Keywords: ISO 14000 Series Standards.; Environmental protection -- Standards.; elektronické knihy; electronic books